EDUKASI PENCEGAHAN DAN PENANGANAN DIMENSIA PADA LANSIA DI UPTD PELAYANAN SOSIAL LANJUT USIA BINJAI DINAS SOSIAL PROVINSI SUMATERA UTARA - Srilasmawanti Srilasmawanti; Lia Mayang Sari Sijabat (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2026)
Dementia is a common health issue among older adults that leads to a decline in cognitive function, independence, and quality of life. Older adults’ limited knowledge of risk factors, signs, and symptoms, as well as preventive measures, has resulted in suboptimal early detection and management of dementia. This community service activity aims to improve older adults’ knowledge and awareness regarding the prevention and management of dementia through health education. The activity was held on June 11, 2026, at the Binjai Elderly Social Services Unit (UPTD) of the North Sumatra Provincial Social Affairs Office, involving 43 older adults. The methods used included a pretest, interactive lectures, discussions, demonstrations, cognitive stimulation exercises, distribution of educational leaflets, and a posttest for evaluation. The results of the activity showed an increase in participants’ knowledge after attending the educational session. Before the activity, most participants still had limited knowledge about dementia, whereas after the activity, the majority of participants understood the definition of dementia, its risk factors, signs and symptoms, preventive measures, and the importance of early detection and regular cognitive stimulation. In addition to increasing knowledge, this program also boosted older adults’ participation, motivation, and awareness regarding the adoption of healthy lifestyle behaviors to maintain cognitive function. Thus, health education has proven to be an effective promotive and preventive strategy for enhancing knowledge and supporting dementia prevention efforts among older adults. Similar programs should be conducted on an ongoing basis as part of older adult health care services.